Transzygomatic Approach to the Tentorial Incisura: Surgical Anatomy - Ammirati, Mario (1992)
A simple transzygomatic approach to the middle fossa centered on the inferior retraction of the temporal muscle after transection of the zygomatic arch is described. This approach allows a very low basal exposure of the middle and temporal fossa, minimizing the amount of temporal lobe retraction needed to approach intradural and extradural lesion in this location. This approach is simple, easily performed, does not require extensive skull base removal, and still offers excellent visualization of the middle fossa and of the region of the tentorial incisura.